Factors associated with inappropriate reduced doses of non-vita-min K antagonist oral anticoagulants in patients with atrial fibrillation - V. A. Ionin; O. I. Bliznuk; V. A. Pavlova; E. I. Baranova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The objective was to study the factors associated with inappropriate reduced doses of non-vitamin K antagonist oral anticoagulants (NOACs) in patients with non-valvular atrial fibrillation (AF) in real outpatient practice.Methods and materials. 10663 case histories of patients hospitalized to the therapeutic clinic of the university for 5 years (2014 — 2018) were studied, 1307/10663 (12,3 %) case histories of patients with AF were selected. Factors associated with inappropriate low doses of anticoagulant therapy (ACT) with NOACs at prehospital treatment were studied.Results. NOACs received 57.7 % (384/665) of patients with AF at the outpatient stage: rivaroxaban — 180/384 (46.9 %) patients, dabigatran etexilate — 110/384 (28.6 %) patients, apixaban — 94/384 (24.5 %) patients. Inappropriate reduced doses of NOACs were revealed in 68/384 (17.7 %) patients: apixaban — 22/94 (23.4 %), dabigatran — 18/110 (16,4 %) and rivaroxaban — 28/180 (15.6 %) (p>0,05). Patients who received inappropriate reduced doses of NOACs as compared to those who received standard doses of NOACs had higher frequency of major bleedings in the past (7.4 and 1.0 %; p=0.014) and had higher risk of bleedings (HAS-BLED 1.7±1,1 and 1.2±1.0; p = 0.0002). Proportion of patients who had HAS-BLED≥3 in these groups were 19.1 % and 8.6 % (p=0.033). All patients who received inappropriate reduced doses of NOACs had modifiable risk factors of bleedings. 85.3 % of patients with AF who received inappropriate reduced doses of NOACs had high risk of stroke according to CHA2DS2-VASc scale.Conclusion. In real outpatient practice, NOACs were recommended to 57.7 % of patients with AF. 17.7 % of patients received NOACs s in inappropriate reduced doses. Frequency of major bleedings in the past and bleeding risk in AF patients with inappropriate reduced doses was higher than in patients with standard doses.